2003
DOI: 10.1093/jee/96.2.456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure Duration on Transfer of Nonrepellent Termiticides Among Workers of Coptotermes formosanus Shiraki (Isoptera: Rhinotermitidae)

Abstract: The potential for transfer of nonrepellent termiticide toxicants between workers of the Formosan subterranean termite, Coptotermes formosanus Shiraki, was examined using two commercially available pesticide formulations and a simple donor-recipient model modified from current methods in the literature. Pesticides used were imidacloprid, formulated as Premise 75 WP, and fipronil, formulated as Termidor SC, in concentrations of 1, 10, and 100 ppm (weight of active ingredient/weight of sand) in sand. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 8 publications
2
68
1
Order By: Relevance
“…Meanwhile, imidacloprid could be transferred among individuals of C. formosanus. 25) The mechanism by which acetamiprid acts on insects is similar to that of imidacloprid. 26) Zhang et al 10) reported that sublethal concentrations of acetamiprid had no effect on the cellulase activity of R. flaviceps workers.…”
Section: Anti-tunneling Effect Of Acetamiprid On Worker Termitesmentioning
confidence: 99%
“…Meanwhile, imidacloprid could be transferred among individuals of C. formosanus. 25) The mechanism by which acetamiprid acts on insects is similar to that of imidacloprid. 26) Zhang et al 10) reported that sublethal concentrations of acetamiprid had no effect on the cellulase activity of R. flaviceps workers.…”
Section: Anti-tunneling Effect Of Acetamiprid On Worker Termitesmentioning
confidence: 99%
“…The author interpreted these data as demonstrating the significance of horizontal transfer in the former case, and its reduction or absence in the latter. Shelton and Grace (2003) also demonstrated significant but minimal transfer of the non-repellent termiticides fipronil and imidacloprid between donors and recipients in laboratory tests. The pathway of horizontal transfer of insecticides is not always clear, though the concentration and exposure period of donors to recipients have been shown to have a significant impact on mortality in C. formosanus with the insecticide indoxacarb (Hu et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…It is known to inhibit the neurotransmitter γ-aminobutyric acid (GABA) in both insects and vertebrates Hosie et al [31,32] Tingle et al [33]. Fipronil and imidacloprid, as non-repellent insecticides, have attracted more interest than traditional repellent insecticides Kard et al [34][35][36][37].…”
Section: /7mentioning
confidence: 99%